Optimal cut-off value of serum procalcitonin in predicting bacterial infection induced acute exacerbation in chronic obstructive pulmonary disease: A prospective observational study. (6th June 2022) - Ye, Yan-Ping; Zhao, Hang; Kang, Tao; Zhao, Li-Hua; Li, Ning; Chen, Jing; Peng, Xiao-Xia
Objective: To explore the optimal cut-off value of serum procalcitonin (PCT) level in predicting bacterial infection in hospitalized patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD). Methods: 204 hospitalized patients with AECOPD were enrolled in this study. Their diagnoses and treatments followed routine protocols in Fu-Xing Hospital affiliated to Capital Medical University, Beijing, China. Extra blood samples were taken for serum PCT level testing and the results were blinded to the treating physicians. On discharge, clinical data were collected and the treating physicians made comprehensive analyses to determine whether the AECOPD were triggered by respiratory tract bacterial infection or non-bacterial causes according to the "new diagnostic criteria" defined in this study. In the AECOPD patients with bacterial infection, treating physicians decided whether they had bacterial pneumonia based on imaging studies. Receiver operating characteristic curve (ROC) was used to analyze the accuracy of serum PCT level in predicting bacterial infection. Results: In the 173 AECOPD patients who did not have pneumonia, 115 had evidences of bacterial infection while 58 did not. The median PCT levels were 0.1(0.08, 0.18) ng/ml and 0.07 (0.05, 0.08) ng/ml for each group, which were statistically different. The proposed optimal cut-off value of serum PCT level in predicting bacterial infection was 0.08 ng/mL according to this study, with a sensitivity of 81%, specificity of 67% and area under the ROC curve (AUC) of 0.794. There were 31 AECOPD patients diagnosed with pneumonia, their median PCT level was 0.23 ng/mL. Conclusions: The serum PCT levels slightly increased in the majority of hospitalized patients with AECOPD compared with reference range. When PCT level was ≥0.08 ng/mL, AECOPD was more likely to be caused by bacterial infection. A significantly elevated PCT levels may indicate combination of AECOPD and bacterial pneumonia.